The Southeastern Librarian, Vol.33, No.3, Fall 1983 - Lucas, Linda (The Southeastern Library Association, 1983)
The Southeastern Librarian, Vol.33, No.03, Fall 1983. Periodical.
1 electronic record. 28 pages. Scanned from original document. Contents Include: Linda Lucas- Editor's Page- 55, Barratt Wilkins- From the President's Desk- 57, Douglas Birkhead- Library Technology: Speaking Up on the " Quiet Revolution"- 58, Barbara Kasper and Robert Smith- The Effect of State Tax Support on Library Service to Children in Rural Areas: A Case Study- 60, Prabha Sharma and Gerald C. Wheelock- An Examination of the Position of Female and Male Librarians in Academic Libraries in Alabama, Georgia, and Mississippi- 65, William K. Black- Performance Appraisal in Libraries: A Staff-Oriented Approach- 69, SELA Chronicle- 72
Keywords: Periodicals | Southeastern Library Association